A Model of Socialist Industrial Wage Differentials: The Case of East Germany - Gregory, Paul (Quarterly Journal of Economics, 1973)
I. Introduction, 132. — II. Empirical estimation of the model, 133. — III. Regression results, 135. — IV. An alternate model, 135. — V. Conclusions, 137. — Appendix: East and West German wage data, 1965, 137.